Implementation of outsourcing as a tool for improving the efficiency of enterprise management - Hang, Yang (Харківський національний автомобільно-дорожній університет, 2024)
The application of the proposed system allowed us to achieve the following results: reduction of the repair budget by 4.8%, strengthening of control over the value chain; improvement of reliability and uninterrupted production; ensuring high efficiency in eliminating emergency works and achieving a relatively even workload of own personnel throughout the year; independent performance of most repairs, independence from partners; the possibility of cooperation with highly specialized, highly qualified companies.
Keywords: management; outsourcing; insourcing; enterprise; algorithm; efficiency; mechanism